Buku Panduan Aman untuk Mengajarkan Keterampilan Bina Diri Berpakaian pada Anak Tunagrahita - Adelin Australiati Saragih; Budi Andayani (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2019)
One of the daily living skills that is less acquired by the intellectually disabled children is dressing skill. Mother of the intellectually disabled children very often assist them to put on their dresses. Their mothers are often reluctant to train them to put on their attires appropriately by themselves due to the lack of information on the ways to train appropriate dressing. The objective of this study was to validate guide book AMAN (Anak MAndiri berpakaiaN), which was aimed to be used by mothers to train the self dressing skill to their intellectually disabled children. The validating process of the book was done by applying content validity test by involving 7 expert panelists who scored the contents of the guide book. The implementation of this guide book was studied using quasi experiment method with one group pretest-posttest design involving 15 subjects. The findings indicated that the guide book AMAN has a significant content validity with V values ranging from 0.71 to 0.91 on each aspect of its content. The guide book AMAN potentially increased the parents’ knowledge in training dressing skills to intellectually disabled children with z value of -3.205 (p < 0.05).